Big Sisters and Child Marriage in Sub-Saharan Africa - Erdal Asker; Daniel I. Rees; Jorge Agüero (Institute of Labor Economics (IZA), 2025)
We study the effect of having an older sister on the likelihood that girls in sub-Saharan Africa marry before reaching adulthood. Relying on the randomness of the firstborn sibling's sex, we show that having an older sister (as opposed to an older brother) reduces the likelihood of marrying before the age of 18 by 1.5 percent. In addition, we find that older sisters reduce the likelihood that their younger sisters become sexually active as a teenager, reduce the likelihood that their younger sisters give birth as a teenager, and increase their younger sisters' awareness of HIV/AIDS. The estimated effects on childhood marriage are largest in more conservative societies (as measured by the Social Institutions and Gender Index), suggesting that the protective role played by firstborn sisters can be especially important when access to accurate information about sex and reproductive rights is limited.
Keywords: I12; J12; 330; teenage sexual activity; older sisters; child marriage; reproductive health